Emotional Bond Reflected In Donny’s Character In Baby Reindeer Movie - Na’ilah Farashifah; Hariyono; Rindrah Kartiningsih (Menulis: Jurnal Penelitian Nusantara, 2026)
This study analyzes the representation of emotional bond in Baby Reindeer movie, focusing on Donny’s emotional attachment to his abuser. Emotional bond refers to a strong psychological connection that develops between individuals through repeated emotional interaction, vulnerability, and dependency. Using a qualitative descriptive method, this research examines selected dialogues and scenes to identify patterns of emotional dependency, empathy toward the abuser, cognitive conflict, and self-blame. The findings show that Donny’s attachment is not rooted in genuine affection, but in fear, vulnerability, and the need for validation. The series portrays emotional bonding as a complex psychological condition that keeps individuals connected to harmful relationships even without physical captivity. This study highlights how contemporary media represents emotional entanglement and the psychological impact of abusive dynamics.